Climate change, hurricanes, and sovereign debt in the Caribbean basin - Eduardo A. Cavallo; Santiago Gómez; Ilan Noy; Eric Strobl (Inter-American Development Bank (IDB), 2024)
Caribbean Islands are exposed to hurricanes, the damages of which are projected to intensify due to anthropogenic climate change. The region is also highly indebted. We focus on the interaction between climate change, hurricanes, and public debt. We investigate what the typical impact of Caribbean hurricanes on public debt in the region has been and how anthropogenic climate change has shaped this impact. Our findings show that for the 10 most severe storms, the average increase in debt, measured as the difference between post and pre-storm trends, is about 10 percent. Three years after such a storm, debt levels are 18 percent higher than what would have been expected otherwise. Based on findings from Extreme Weather Event Attribution (EEA) research, we calculate that the impact of a severe hurricane on public debt that is attributable to climate change amounts to an increase of 3.8 percent of the debt stock relative to the level of debt at the time of the event.
Keywords: Q54; 330; Caribbean; Public debt; Hurricanes; Attribution; Climate change